Academician alexei v. simashkevich – 85th jubilee - Şerban, Dormidont (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2014)

(untitled)
June 27, 2014 is a special—85th jubilee—birthday in the life and activity of the Moldovan researcher Alexei V. Simashkevich. He is Full Member of the Academy of Sciences of Moldova, doctor habilitate in physics and mathematics, professor, researcher-consultant of the Institute of Applied Physics of the Academy of Sciences of Moldova (the IAP). Academician Simashkevich has contributed a lot in the development of the Faculty of Physics of Moldova State University (the MSU) and of the IAP, in the progress of semiconductor physics in Moldova, and in training of high-level specialists in physics.